2005
DOI: 10.1177/0363546504267806
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Anterior Cruciate Ligament Reconstruction on Knee Joint Kinematics under Simulated Muscle Loads

Abstract: Decreased internal rotation of the knee after anterior cruciate ligament reconstruction may lead to increased patellofemoral joint contact pressures. Future anterior cruciate ligament reconstruction techniques should aim at restoring 3-dimensional knee kinematics under physiological loads.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
105
2
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 84 publications
(115 citation statements)
references
References 61 publications
7
105
2
1
Order By: Relevance
“…In vivo studies with three-dimensional motion analysis from our laboratory [4][5][6] have demonstrated abnormal rotational knee movement during highly demanding activities after reconstruction of the anterior cruciate ligament. Our results have been verified by both in vitro and in vivo studies from other laboratories 2,7,[11][12][13][14] . Furthermore, authors of in vitro studies have examined the possible causes of this phenomenon and have investigated the effects, on rotational knee kinematics, of the configuration and placement of the graft used to reconstruct the anterior cruciate ligament.…”
Section: Level Of Evidence: Therapeutic Level II See Instructions Tosupporting
confidence: 82%
“…In vivo studies with three-dimensional motion analysis from our laboratory [4][5][6] have demonstrated abnormal rotational knee movement during highly demanding activities after reconstruction of the anterior cruciate ligament. Our results have been verified by both in vitro and in vivo studies from other laboratories 2,7,[11][12][13][14] . Furthermore, authors of in vitro studies have examined the possible causes of this phenomenon and have investigated the effects, on rotational knee kinematics, of the configuration and placement of the graft used to reconstruct the anterior cruciate ligament.…”
Section: Level Of Evidence: Therapeutic Level II See Instructions Tosupporting
confidence: 82%
“…This system can be operated under both force and displacement control modes to study the knee biomechanics. The operation of the robotic testing system has been detailed in several studies in the literature [19,20].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, studies have suggested that the ability of current reconstruction techniques to prevent degenerative changes compared with nonoperative treatment is limited [11,[13][14][15]36]. Although many mechanisms likely contribute to this degeneration (for example, traumatic injury to other soft tissues at the time of ACL rupture), numerous authors suggest the inability of the reconstruction to restore normal joint kinematics is an important factor [17,34,39,50,53,54].…”
Section: Introductionmentioning
confidence: 99%